Kekuatan Modal Sosial dalam Kontestasi Politik Pemilihan Kepala Desa: Studi Kasus Keterpilihan Kepala Desa Kindang Kec. Kindang. Kab. Bulukumba - Jupri Jupri; Nurmiati Nurmiati; Abd Haris; Muhammad Tobar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to explain the strength of social capital owned by Nurdin in political contestation in 2016. This type of research is a descriptive qualitative study to explore the strength of social capital in the transformation of village head leadership. Meanwhile, the approach used is the phenomenological approach The results of this study indicate that the previous leadership style that the author limits only captures the leadership style for the period 2002-2009. During the 2002-2004 period, when Karaeng Oddang was in charge, in his leadership he tried to be more democratic, but the domination of his father (Karaeng Manna) was still strong at that time. Likewise with Aji Awaluddin 's karaeng leadership style, he was a typical leader who was considered by the community to be very good and realized democratic values ​​during his tenure as head of Kindang village for the 2004-2009 period. In 2009-2016, this was where leadership transformation took place. Photographing Nurdin's leadership style for the period of 2009 cannot be separated from appreciation and praise. However, this criticism did not have an impact on the 2016 village head election. Nurdin won the pilkades again. Nurdin's strength of social capital in the election has won him victory. The rise of primordial sentiment among ordinary people (tumaradeka) as Nurdin's strength, and on the other hand the rise of negative stereotypes against karaeng that spread to the issue of group identity and the strong strength of social networking capital, bonding, bridging and linking greatly colored the 2016 pilakdes. Social capital security control is a selling point for Nurdin so that he can get support from the community compared to other candidates who are deemed unfit and unable to anticipate security in Kindang village.